(untitled) (Research, Society and Development, 2020)
The new Coronavirus was defined as SARS-CoV-2 in late 2019. It is responsible for the disease classified as COVID-19. The present study aimed to discuss the deaths caused by covid-19 in the state of Piauí during the pandemic, and its correlation with the comorbidities associated with patients and their age group. It is a descriptive research, carried out from the epidemiological survey of cases and deaths of Covid-19 in the State of Piauí. The age range, comorbidities and risk factors identified among the deaths were analyzed, where from these data, lethality was calculated and plotted in tables. The state of Piauí has10,153 thousand confirmed cases, with the capital Teresina, with the largest number, with 43% of cases followed by the coastal city of Parnaíba with 13%, Barras 4%, Campo Maior 3% and Picos 3%. Teresina still had the highest number of deaths with 196 deaths, followed by Parnaíba (n = 31), Barras (n = 8), Campo Maior (n = 7), Picos, Esperantina and Piripiri (n = 6). Heart diseases had the highest frequency in cases of death by Covid-19, with 48.61% of cases, followed by diabetes with 23.61%, CND or DNM 4.63%, Obesity 3.7%. The age group from 70 to 79 years old most affected with 30%, followed by 80 years old or more with 26.67%. Thus, it can be inferred how essential the structural development of public health in Piauí is, especially in emerging centers, as well as the priority preservation of people who have comorbidities and with high age.